Pengaruh Lama Waktu Fermentasi Terhadap Total Flavonoid Dan Uji Organoleptik Kombucha Teh Hitam Dan Infusa Bunga Telang (Clitoria Ternatea L.) - Putu Rima Sintyadewi; Ida Ayu Putu Ary Widnyani (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2021)
The purpose of this research is to find out the influence of fermentation time on the total flavonoid of black tea kombucha and butterfly pea infusion and to find out panelists’ preferences level on the black tea kombucha and butterfly pea infusion products. Based on the analysis of variance (ANOVA), it is shown that the fermentation time has very significant impact (P>0.01) on the total flavonoid of black tea kombucha and butterfly pea infusion. The interaction between treatments of the combination of black tea and Asian pigeonwings fusion was significantly different from fermentation time (P>0.5). The highest total flavonoid was obtained on the 8thday of fermentation on the P3 (3:3) treatment which was 68,4 mg QE/g extract. Overall, the panelists preferences level on the black tea kombucha and butterfly pea infusion products was 77,5% accepting and 22,5% less accepting. Panelists were able to accept the black tea kombucha and butterfly pea infusion products as fungsional drinks looking at the benefits shown by this drinks product.